2021
DOI: 10.3389/fonc.2021.723509
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Reality and Intraoperative Navigation in Sinonasal Malignancies: A Preclinical Study

Abstract: ObjectiveTo report the first use of a novel projected augmented reality (AR) system in open sinonasal tumor resections in preclinical models and to compare the AR approach with an advanced intraoperative navigation (IN) system.MethodsFour tumor models were created. Five head and neck surgeons participated in the study performing virtual osteotomies. Unguided, AR, IN, and AR + IN simulations were performed. Statistical comparisons between approaches were obtained. Intratumoral cut rate was the main outcome. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…Within the control arm, surgeons utilized Materialise Mimics’ built-in measurement tool for eventual intraoperative reference during implant placement. Whereas in the experimental arm, device placement was projected onto the surgical field using GTx-Eyes (Guided Therapeutics, TECHNA Institute, Canada) via a PicoPro projector (Cellon Inc., South Korea) 7 , 11 . The AR setup is demonstrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the control arm, surgeons utilized Materialise Mimics’ built-in measurement tool for eventual intraoperative reference during implant placement. Whereas in the experimental arm, device placement was projected onto the surgical field using GTx-Eyes (Guided Therapeutics, TECHNA Institute, Canada) via a PicoPro projector (Cellon Inc., South Korea) 7 , 11 . The AR setup is demonstrated in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Surgical simulation software paired with intraoperative navigation (IN) tools have also been utilized 2 , 6 . A major challenge of IN technologies is the omission of relevant information from the surgical field requiring surgeons to switch their focus to and from the surgical field 7 . Augmented reality (AR) guided surgery has been proposed to overcome this by placing relevant information directly into the surgical field 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Sahovaler et al [ 105 ] reported a novel AR system in open sinonasal tumor resections in preclinical skull models and compared it to the more traditional intraoperative navigation systems. Using GTx-Eyes [ 81 ], tumors were projected by an external projector onto the skull surface.…”
Section: The Gtx Lab Experiencementioning
confidence: 99%
“…Rather, it represents a gateway to the critical structures located within the bone of the skull base, since most of the surgical approaches consist in drilling out the bone of the skull base until the target areas are reached. The recent development of virtual surgical planning protocols and image-guided surgery systems have rendered the “surgical corridor” paradigm even more crucial, thus supporting the accurate planning of the surgical trajectory towards the target area and facilitating the anatomical orientation [ 10 , 11 , 12 , 13 , 14 ]. In this setting, augmented reality visualization modalities may represent a new frontier in which to further improve the benefits provided by the image-guided surgery paradigm [ 12 , 13 , 15 ].…”
mentioning
confidence: 99%
“…The recent development of virtual surgical planning protocols and image-guided surgery systems have rendered the “surgical corridor” paradigm even more crucial, thus supporting the accurate planning of the surgical trajectory towards the target area and facilitating the anatomical orientation [ 10 , 11 , 12 , 13 , 14 ]. In this setting, augmented reality visualization modalities may represent a new frontier in which to further improve the benefits provided by the image-guided surgery paradigm [ 12 , 13 , 15 ].…”
mentioning
confidence: 99%